2020
DOI: 10.1155/2020/8467406
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Croton macrostachyus Stem Bark Extract and Solvent Fractions on Cyclophosphamide‐Induced Cardiotoxicity in Rats

Abstract: Context. Croton macrostachyus Hochst. ex Delile (Euphorbiaceae) has been used in traditional medicine to manage heart failure and other heart diseases in Ethiopia. Objective. To evaluate the antioxidant and cardioprotective activities of stem bark extract and solvent fractions of Croton macrostachyus on cyclophosphamide-induced cardiotoxicity in rats. Materials and Methods. DPPH free radical scavenging assay method was used to determine antioxidant activity whereas Sprague-Dawley rats were used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…All treatment groups prevented increases in kidney-to-body weight ratio compared to cyclophosphamide-treated group. The antioxidant activity 24 of Croton macrostachyus might be the reason for the prevention of kidney and kidney-to-body weight increment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All treatment groups prevented increases in kidney-to-body weight ratio compared to cyclophosphamide-treated group. The antioxidant activity 24 of Croton macrostachyus might be the reason for the prevention of kidney and kidney-to-body weight increment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the plant showed anti-bacterial, 21 anti-diarrheal, 13 anti-malarial, 22 anti-convulsant, 23 antidiabetic 16 and cardioprotective activity. 24 The phytochemical screening demonstrated that stem bark of Croton macrostachyus constituted major secondary metabolites such as, tannins, steroids, alkaloids, phenols, terpenoids, saponins, and flavonoids, which may be the reason for the plants' widespread pharmacological activity. 25 In Ethiopian traditional medicine, Croton macrostachyus has been widely used to manage renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Ayza et al [62] Either sex of Sprague Dawley rats Animals were treated with a single dose of CP (200 mg/kg, i.p.) on the first day followed by hydromethanolic crude extract and solvent fractions of Croton macrostachyus for 10 days.…”
Section: Concurrent Administration Of Sly and Cur Withmentioning
confidence: 99%
“…They were also found to activate a cellular redox defense mechanism by stimulating endogenous antioxidant fractions [32] and keep the cells from xenobiotic oxidative stress, DNA impairment, and apoptosis [33]. Much attention has been given to using plant chemicals as a defensive strategy to resolve cardiotoxicity triggered by DOX [34][35][36].…”
Section: Introductionmentioning
confidence: 99%